1986
DOI: 10.1177/014107688607900504
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal Surgery for Cushing's Disease

Abstract: SummaryA series of 101 patients with Cushing's disease underwent transsphenoidal surgery. Diagnosis was fundamentally based on dynamic testing, mainly on the dosage-dependent suppression of cortisol after dexamethasone. The effect of surgery was monitored by intraoperative ACTH measurements. In 96 out of 101 patients a microadenoma of the pituitary was identified and removed selectively. In 74% of patients there was a clinical and endocrinological remission of Cushing's disease. Four 'operative failures' after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(84 citation statements)
references
References 29 publications
6
76
0
2
Order By: Relevance
“…the thromboembolic events were related to surgery, whereas VTE unrelated to surgery was reported in 44% of the patients with CS (9,14,15,32,36,38,39,40,47,48,49,50,51). VTE was reported as the cause of death in 11% (13/121) of the patients with CS.…”
Section: :4 M16mentioning
confidence: 99%
“…the thromboembolic events were related to surgery, whereas VTE unrelated to surgery was reported in 44% of the patients with CS (9,14,15,32,36,38,39,40,47,48,49,50,51). VTE was reported as the cause of death in 11% (13/121) of the patients with CS.…”
Section: :4 M16mentioning
confidence: 99%
“…Assie et al and Xing et al reported a lower incidence of cavernous sinus invasion [3,12]. Other authors have pointed out that the main factor influencing the effectiveness of surgical treatment, and highly important in terms of prognosis, is the degree of extrasellar expansion [3,25]. Suprasellar growth together with visual disturbances resulting from optic chiasm compression occurs quite frequently in NS [5,7].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Bogan et al suggested that "normal cortisol levels" in a 2-mg overnight dexamethasone test should be considered criteria for cure (52). Similarly, Fahlbusch et al reported that levels less than 2 µg/dl are good predictors of cure (53). Other studies suggest that values of < 3 µg/dl (26), < 5 µg/dl (69), < 100 nmol/l (25), or < 8 µg/dl (70) could better identify those patients on CD remission.…”
Section: Low-dose Dexamethasone Cortisol Suppressionmentioning
confidence: 99%